Being an Authorized User: What It Won't Do for Your Credit Score - Michael S. Gutter (EDIS)
FCS-7228, a 2-page fact sheet by Michael S. Gutter, discusses recent changes in the way being an authorized user affects a person’s credit score. Published by the UF Department of Family Youth and Community Sciences, September 2008.